2018
DOI: 10.1007/s11239-018-1637-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of oral anticoagulants in patients with sickle cell disease and venous thromboembolism: a retrospective cohort study

Abstract: Patients with sickle cell disease (SCD) experience initial and recurrent venous thromboembolism (VTE) more commonly and at a younger age than the general population, and it confers a higher mortality for patients with SCD. However, limited evidence is available to guide anticoagulant use for VTE treatment in this population. The primary objective of this study is to characterize the effectiveness and safety of direct oral anticoagulants (DOAC) and warfarin for VTE treatment among patients with SCD. This single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Of those on warfarin, 1 of 15 patients (7%) developed major bleeding and 2 of 15 (13%) developed nonmajor bleeding. 121 In another cohort study of individuals with SCD on anticoagulation (n 5 877), the cumulative incidence of bleeding was 4.9% (95% CI, 3.5%-6.4%) at 6 months and 7.9% (95% CI, 6.2%-9.8%) at 1 year. 123 Benefits, harms, and burden.…”
Section: Indefinite Anticoagulation Is Not Recommended For Firstmentioning
confidence: 95%
See 1 more Smart Citation
“…Of those on warfarin, 1 of 15 patients (7%) developed major bleeding and 2 of 15 (13%) developed nonmajor bleeding. 121 In another cohort study of individuals with SCD on anticoagulation (n 5 877), the cumulative incidence of bleeding was 4.9% (95% CI, 3.5%-6.4%) at 6 months and 7.9% (95% CI, 6.2%-9.8%) at 1 year. 123 Benefits, harms, and burden.…”
Section: Indefinite Anticoagulation Is Not Recommended For Firstmentioning
confidence: 95%
“…A total of 3 published studies reported on safety of anticoagulation in adults with SCD. [121][122][123] In a retrospective study of patients with SCD receiving VTE prophylaxis (n 5 116), anticoagulation was discontinued for hemorrhage in 5 of 116 patients (4.3%). 122 In a small retrospective cohort study of patients receiving oral anticoagulants (n 5 37), 3 of 22 patients (14%) receiving direct oral anticoagulants developed nonmajor bleeding and none developed major bleeding.…”
Section: Indefinite Anticoagulation Is Not Recommended For Firstmentioning
confidence: 99%
“…A recently published single institution retrospective study of 37 SCD patients with VTE, treated with anticoagulation, revealed a high incidence of recurrence and bleeding . Nine patients developed VTE recurrence within six months of the index event (24%).…”
Section: Discussionmentioning
confidence: 99%
“…Three types of anticoagulation have been tested. 59 Warfarin and acenocoumarin reduce the markers of coagulation activation but have no effect on the frequency of painful episodes. Low molecular weight heparin (HPBM) decreases the severity of painful crises and, as a consequence, the duration of hospital stay.…”
Section: Results (Recommendations and Guidelines)mentioning
confidence: 99%